Effectiveness of Massage Including Proximal Trigger Point Release for Plantar Fasciitis: a Case Report - Juchli, RMT, Lydia (International Journal of Therapeutic Massage & Bodywork, 2021)
Background: Plantar fasciitis (PF) is a common degenerative condition of the plantar fascia. Symptoms include tenderness on the plantar surface of the foot, pain on walking after inactivity, and difficulty with daily activities. Rest, non-steroidal anti-inflammatories, and manual therapies are frequently used treatments for PF. Trigger point release (TrPR) for PF has been found as a viable treatment option. Objective: To determine the effects of massage, including proximal TrPR, for pain and functional limitations in a patient with PF. Method: A student massage therapist from MacEwan University administered five massages, one initial and one final assessment over five weeks to a 46-yearold female with diagnosed PF. She complained of unilateral plantar heel pain (PHP) and deep pulling from mid-glutes to the distal lower limb bilaterally. Evaluation involved active and passive range of motion, myotomes, dermatomes, reflexes, and orthopedic tests. The treatment aim was to decrease PHP by releasing active trigger points (TrPs) along the posterior lower extremity to the plantar surface of the foot, lengthening the associated muscles and plantar fascia. Hydrotherapy, Swedish massage, TrPR, myofascial release, and stretches were implemented. Pain was measured using the numerical rating scale pre- and post-treatments, and the Foot Function Index was used to assess function at the first, middle, and last appointments to assess the effectiveness of massage including proximal TrPR for PF. Results: PHP and functional impairments decreased throughout the fiveweek period. Conclusion: The results indicate massage, including proximal TrPR, may decrease pain and functional impairments in patients with PF. Further research is necessary to measure its efficacy and confirm TrPR as a treatment option.